(untitled) (PROCEEDING OF INTERNATIONAL CONFERENCE ON MULTIDISCIPLINARY STUDY, 2025)
Study This aiming For know influence compensation , training , discipline and environment Work to performance employee of the Investment and Services Office One Stop Integrated Regency Kerinci . Karimun . Population in the study This is all over employee of the Investment and Services Office One Stop Integrated Regency Karimun, which consists of 60 people and the taking of sample use technique census . Type study This is study quantitative and use design study analysis descriptive . Method collection instruments used​ is distribution questionnaire through Google Form . Research results This show that compensation influential positive and significant on the Performance of Employees of the Investment and Services Office One Stop Integrated Regency Karimun mark t count 2.263 > t table 2.004 and value significance 0.000 < 0.05. Training influential positive and significant to performance employee of the Investment and Services Office One Stop Integrated Regency Karimun mark t count 8.833 > t table 2.004 and the value significant 0.000 < 0.05. Discipline influential positive and significant to performance employee of the Investment and Services Office One Stop Integrated Regency Karimun T value is 4.060 more big from table 2.004 and values significance 0.000 < 0.05. Environment Work influential positive and significant to performance employee of the Investment and Services Office One Stop Integrated Regency Karimun . Work t count 2.520 > t table 2.004 and the value significance 0.015 > 0.05. Compensation , training , discipline , and work environment Work in a way simultaneous influential significant to performance employee the latest service One door inner accept . This is can seen from mark F count 525.473 > F table 2,537 with level significant 0.000 > 0.05.